(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the proposed work a fuzzy based power stabilizer is to be designed for a single machine infinite bus bar (SMIB) system. The whole work is to be carried out in MATLAB. The simulations are to be carried out on a state space model of SMIB Energy system with fuzzy logic controller and conventional controller in the presence of small disturbance in the system. The effectiveness (steady state error, overshoot settling time) of fuzzy controller is to be compared with the conventional PSS. Further the complexity of proposed fuzzy PSS may be reduced by reducing the number of fuzzy rules. This simple design approach and smaller rule base is easy to realize and can provide better performance compared with the conventional power system stabilizer and fuzzy logic power system stabilizer.